2019
DOI: 10.1186/s40543-019-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated sour cherry kernel shell beads: an adsorbent for removal of Cr(VI) from acidic solutions

Abstract: In this study, a composite biosorbent in the form of beads was produced from chitosan and the powder of sour cherry kernel shells. Characterization of chitosan-coated sour cherry kernel shell beads was done using elemental analysis, FT-IR spectroscopy, SEM, and EDX spectrum analysis. Adsorption capacity of chitosan-coated sour cherry kernel shell beads was tested in removal of Cr(VI) under different conditions, pH 2.0-7.0, adsorbent dosage 0.01-0. 20 g, initial Cr(VI) ion concentration 10-315 mg L −1 , tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…As can be seen in Figure 7, the absorption rate was elevated from 15 to 120 minutes. By prolonging the contact time, the adsorption capacity of the adsorbent would not increase considerably (Altun 2019). From the time of contact, it can be concluded that the absorption rate initially increased and then equilibrated (Wu et al 2019).…”
Section: Effect Of Contact Timementioning
confidence: 98%
“…As can be seen in Figure 7, the absorption rate was elevated from 15 to 120 minutes. By prolonging the contact time, the adsorption capacity of the adsorbent would not increase considerably (Altun 2019). From the time of contact, it can be concluded that the absorption rate initially increased and then equilibrated (Wu et al 2019).…”
Section: Effect Of Contact Timementioning
confidence: 98%
“…CS is a natural linear polysaccharide consisting of randomly dispersed β-(1-4-D-glucosamine and N-acetyl-D-glucosamine [7]. The free amino and hydroxyl groups of CS cause its solubility in acidic solutions for chemical functionalization [8]. CS possesses diverse activities such as biocompatibility, biodegradability, nontoxicity, anti-inflammatory, antihypertensive, and antimicrobial behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are one of the persistent and most toxic pollutants found in industrial wastewaters. Chromium is one such toxic heavy metal released into freshwater bodies from industries like leather tanning, electroplating, and steel manufacturing (Altun 2019). According to WHO, 0.05 mg L −1 is the permissible limit of chromium in freshwater.…”
Section: Introductionmentioning
confidence: 99%